Relações de precipitações-umidade do solo-vazão de eventos sub-diários em bacias experimentais do NE Brasileiro - Barbosa, Luís Romero (2015)
The assessment of rainfall-runoff transformation mechanisms with high temporal resolution data has proven crucial to the improving of hydrological studies, by providing detailed knowledge and information about the properties and the characteristics of their main variables. This study aimed at assessing the influence of rainfall event definition criteria in determining the characteristics of hyetographs, as well as in investigating the hydrological relations of rainfall events and antecedent soil moisture with those of the runoff hydrograph, by means of statistical techniques, in experimental basins in Northeast Brazil. To this end, a portion of the data was acquired, in sub-hourly scale, from the databases maintained by the partners of the research since 2003 and the other one was monitored and taken along the hydrological year of 2013-2014 through frequent measurements, performing essays and data processing. Then, descriptive statistics, hypothesis testing, exploratory data analysis, multivariate statistical techniques and multiple linear regression were carried out either for visual inspection or for statistical data investigation, in order to establish variation patterns and evaluate the association degree among variables. The first study revealed that the variation in minimum inter-event time criteria has reduced by almost 50% the number of events, and underestimated the average intensity of events by 4 times on average. The second study showed that the tropical coastal basin has approximately 4 times more events than those of semiarid, of which 6% of all events that remain unshaped, contribute to 38% of the total precipitation, and could be reduced by up to 97%, becoming mainly on unimodal events with peak to the left. The third study showed that soil moisture has a similar variation pattern up to 3 days in advance and exerts a significant influence, along with the precipitation and duration of rainfall events on both the runoff coefficient, the peak and the discharge of hydrographs; on the other hand, the principal component responsible for the peak and intensities of hyetographs was significant only on the runoff coefficient, which was, in turn, the best feature set for the multiple linear regression analysis, as it the coefficient of determination was 0.66. Therefore, this study highlights the importance of continuous and systematic hydro-climatological data monitoring for the experimental studies that may provide input to decision-making in water resources management measures.